Interventional Neuroradiology - Murphy, Kieran; Robertson, Fergus (Techniques in Interventional Radiology, 2014)
The objective of the Techniques in Interventional Radiology series is to provide easily accessible technique specific information on interventional radiology procedures, suitable for reference in the IR room or as a carry-around guide. Each volume has an EU and US editor so that the perspectives presented are balanced across these two major centres of interventional radiology. Each volume has a consistent template for easy and quick reference, with step-by-step bullet points, key point summaries at the end of each chapter and illustrations/line drawings as a visual aid. Interventional Neuroradiology will bring to the fore the collective wisdom of specialist interventional neuroradiologists, for their own reference and more crucially for the reference of trainees in interventional neuroradiology. This book will appeal to those already practising interventional neuroradiology and those taking fellowships in the speciality from neurology, neurosurgery or neuroradiology.